Improving Employee Engagement Through Organizational Culture and Servant Leadership with Commitment Towards the Organization as an Intervening Variable on Employees of a Private Hospital in Bogor Regency - Eka Verawati; Widodo Sunaryo; Herdiyana Herdiyana (Indonesian Interdisciplinary Journal of Sharia Economics)
This study aims to improve employee engagement at a private hospital in Bogor Regency through organizational culture and servant leadership with commitment to the organization as an intervening variable. The study population was 141 permanent employees at the staff level and the number of samples used was 105 employees. Data collection to measure employee engagement variables, organizational culture, servant leadership and commitment to the organization was in the form of a questionnaire. Data analysis techniques used descriptive statistics and path analysis. The results of the study showed: (a) There is a positive direct effect of organizational culture on commitment to the organization (b) There is a positive direct effect of servant leadership on commitment to the organization. (c) There is a positive direct effect of organizational culture on employee engagement. (d) There is a positive direct effect of servant leadership on employee engagement. (e) There is a positive direct effect of commitment to the organization on employee engagement (f) There is a positive indirect effect of organizational culture on employee engagement through commitment to the organization. (g) There is a positive indirect effect of servant leadership on employee engagement through commitment to the organization.